Cognition and Cerebrovascular Reactivity in Midlife Women With History of Preeclampsia and Placental Evidence of Maternal Vascular Malperfusion - Shaaban, C. Elizabeth; Rosano, Caterina; Cohen, Ann D.; Huppert, Theodore; Butters, Meryl A.; Hengenius, James; Parks, W. Tony; Catov, Janet M. (Frontiers in Aging Neuroscience, 2021)
Background: Preeclampsia is emerging as a sex-specific risk factor for cerebral small vessel disease (SVD) and dementia, but the reason is unknown. We assessed the relationship of maternal vascular malperfusion (MVM), a marker of placental SVD, with cognition and cerebral SVD in women with and without preeclampsia. We hypothesized women with both preeclampsia and MVM would perform worst on information processing speed and executive function. Methods: Women (n=45; mean 10.5 years post-delivery; mean age: 41 years; 42.2% Black) were classified as preeclampsia-/MVM-, preeclampsia+/MVM-, or preeclampsia+/MVM+. Information processing speed, executive function, and memory were assessed. In a pilot sub-study of cerebrovascular reactivity (CVR; n=22), cerebral blood flow during room-air breathing and breath-hold induced hypercapnia were obtained via arterial spin labeling MRI. Non-parametric tests and regression models were used to test associations. Results: Between-group cognitive differences were significant for information processing speed (p=0.02); preeclampsia+/MVM+ had the lowest scores. Cerebral blood flow increased from room-air to breath-hold, globally and in all regions in the three groups, except the preeclampsia+/MVM+ parietal region (p=0.12). Lower parietal CVR (less change from room-air breathing to breath-holding) was correlated with poorer information processing speed (partial ρ=0.63, p=0.005) and executive function (ρ=0.50, p=0.03) independent of preeclampsia/MVM status. Conclusions: Compared to women without preeclampsia and MVM, midlife women with both preeclampsia and MVM have worse information processing speed and may have blunted parietal CVR, an area important for information processing speed and executive function. MVM in women with preeclampsia is a promising sex-specific indicator of cerebrovascular integrity in midlife.